Brief communication: Stream microbes preferentially respire young carbon within the ancient glacier dissolved organic carbon pool - A. D. Holt; A. D. Holt; A. D. Holt; A. D. Holt; J. B. Fellman; J. B. Fellman; A. M. Kellerman; A. M. Kellerman; E. Hood; E. Hood; S. H. Bosman; A. M. McKenna; et al. (The Cryosphere, 2025)
Glaciers export ancient bioavailable dissolved organic carbon (DOC). Yet, the sources of organic carbon (OC) underpinning bioavailability are poorly constrained. We assessed the isotopic composition of respired OC from bioincubations of glacier DOC. Relative to bulk DOC, respired OC was younger (+4350 to 8940 years) and 13C enriched (+9.2 ‰ to 12.2 ‰), consistent with utilization of an in situ-produced microbial carbon source. These findings provide direct evidence that a hidden pool of young OC may underpin the high bioavailability of ancient glacier DOC.